A rich catalog of C–C bonded species formed in CO2 reduction on a plasmonic photocatalyst - Dinumol Devasia (Nature Portfolio, 2021)
In situ vibrational spectroscopy affords a powerful tool for probing elementary chemical processes on catalytic surfaces. Using surface enhanced Raman scattering, authors identify an array of multicarbon species formed on a Ag nanoparticle catalyst in plasmon-driven reduction of CO2 in water.